Increasing the cyber resilience of SMEs through open-source solutions and international collaboration - Ionica ȘERBAN; Florentina-Mihaela CURCĂ; Robert-Ștefan ȘANDRU (Bulletin of "Carol I" National Defense University)
In an increasingly digitalized world, small and medium-sized enterprises (SMEs) are exposed to significant cyber threats due to limited security resources. This article explores the role of open-source solutions and international collaboration in enhancing the cyber resilience of SMEs. Open-source solutions offer financial accessibility, flexibility, and increased security, supported by global communities that contribute to their continuous improvement. Moreover, decentralized sharing of threat information, combined with artificial intelligence, enables more efficient detection and prevention of cyberattacks. Through collaborative initiatives such as HackOlympics, SMEs can learn through hands-on experience and benefit from solutions tested in real-life scenarios. In conclusion, open-source solutions and the use of advanced technologies, such as AI, provide SMEs with an effective strategy to address modern cyber challenges, improving their resilience and protection against threats.